The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1007/s40120-022-00418-9
|View full text |Cite|
|
Sign up to set email alerts
|

Multiple Sclerosis and Neuromyelitis Optica Spectrum Disorder: Onset Following Acute COVID-19 Infection, a Case Series

Abstract: Background and Objectives: Acute COVID-19 infection has been associated with neurological involvement. We report a case series of newly diagnosed patients with multiple sclerosis (MS) and neuromyelitis optica spectrum disorder (NMOSD) developed in a short period of time after acute COVID-19 infection. Methods: New MS patients developing initial symptoms shortly after an acute COVID-19 infection were diagnosed based on the 2017 McDonald Criteria [Garcia-Ramos et al. in Cells, 2021]. The patients diagnosed with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The use of the most comprehensive COVID-19 phenotype data to date by Baranova et al. makes their findings more reliable and consistent with certain case reports or case series observations ( 6 , 42 , 43 ).…”
Section: Discussionmentioning
confidence: 60%
“…The use of the most comprehensive COVID-19 phenotype data to date by Baranova et al. makes their findings more reliable and consistent with certain case reports or case series observations ( 6 , 42 , 43 ).…”
Section: Discussionmentioning
confidence: 60%
“…Both from our experience and a review of the cases reported in the literature, viral/vaccine exposure is more strongly associated with MS onset than with disease reactivation [ 49 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ]. The most plausible explanation is the protective effect of DMTs against the inflammatory activation of the immune system known to be triggered by viral infection/vaccination.…”
Section: Discussionmentioning
confidence: 95%
“…Even though it is impossible to attribute a definite causal role for MS onset to SARS-CoV-2 and the related vaccines, several cases have been reported both after COVID-19 (8 case reports, 3 case series, Table 1 ) and after anti-SARS-CoV-2 vaccines exposure (13 case reports, 6 case series, Table 2 ) [ 49 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ]. Cases of post-viral infection MS onset or relapse presented with clinical symptoms suggestive for demyelinating disorders after a few days to 6 weeks from viral exposure, except for one case in which the viral infection preceded the disease onset by 6 months [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…development after COVID-19 in unvaccinated patients(Avila et al, 2023;Pignolo et al, 2021;Palao et al, 2020). A systematic review found 18 cases of MOGAD following infection(Mirmosayyeb et al, 2023), while another one revealed 15 cases of NMOSD(Harel et al, 2023).…”
mentioning
confidence: 99%